Accounting Conservatism and the Temporal Trends in Current Earnings’ Ability to Predict Future Cash Flows versus Future Earnings: Evidence on the Trade‐off between Relevance and Reliability - BANDYOPADHYAY, SATI P.; CHEN, CHANGLING; HUANG, ALAN G.; JHA, RANJINI (Contemporary Accounting Research, 2010)
This research reports that an increasing level of accounting conservatism over the 1973–2005 period is associated with: (1) an increase in the ability of current earnings to predict future cash flows and (2) a decrease in the ability of current earnings to predict future earnings. We also find that usefulness of earnings for explaining stock prices over book values is positively related to reliability but not to relevance. Our results hold for the constant and full samples in both in‐sample and out‐of‐sample analyses and are robust to the use of alternative measures for relevance, reliability, earnings usefulness, and conservatism. Our findings about the relations among conservatism, relevance, reliability, and usefulness suggest a trade‐off between relevance and reliability and seem to indicate that the adoption of an increasing number of conservative accounting standards has a possible adverse impact on earnings usefulness through a negative effect on reliability.